CHANGE OF RUSSIA’S COMPETITIVE POSITIONS IN THE WORLD MARKET OF SPACE PRODUCTS - A. P. Krishtofor (Publishing House of the State University of Management, 2019)
Subject of research – the Russian space industry against the background of the main trends of development of the world market of space products. Research objective – to give an assessment to specifics of the competition in the main segments of the world space industry and to consider the main trends of development of the Russian space industry. The result of research is that at the present stage big changes of an environment of the world space market are observed, and also competitive positions of Russia in world private and state astronautics have been scientifically substantiated and generalized. The transnational companies in the industry become more flexible and strive to provide high level of quality of the activity. In the Russian space industry more intent attention is required to quality of industrial management.